SERUM AFP (ALPHA FETO PROTEIN) LEVELS PROFILE OF HEPATOCELLULAR CARCINOMA PATIENTS IN DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA - Putri, Dyeneka Rustanti Indreswara; Maimunah, Ummi; Retnowati, Endang (Universitas Airlangga, Surabaya, Indonesia, 2022)
Higlight:1. The USG results of AFP level can be used for early detection and therapy of hepatocellular carcinoma that can prevent metastasis, progressivity, and recurrence. 2. The most common patients with high AFP levels are those with hepatitis B depending on etiology, younger age, male, gender, high SGOT level and BCLC B patients.Abstract:Background: Hepatocellular carcinoma (HCC) accounts for more than 90% of liver cancer which is the second most common cause of cancer-related death worldwide. The incidence of HCC was 626.000 cases every year worldwide. Early detection and therapy can prevent metastasis, progressivity, and recurrence. AFP level â‰¥ 400 ng/ml and USG results can be used as a diagnosis parameter of hepatocellular carcinoma. Objective: To analyze the AFP level's profile in hepatocellular carcinoma. Materials and Methods: Descriptive methods used in this study with data collected from medical records on patients that fulfilled the inclusion criteria in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia during the periods of 1st January 2013- December 31st 2015. This study used various variables such as age, gender, etiology and size of the tumor, number of a nodule, hepatic function with child classification, staging BCLC, and AFP level. Results: This study found that the 98 patients with hepatocellular carcinoma with high AFP level or >400 ng/ml were dominated by younger patients with average age of 49.91 years, the most common etiology was hepatitis B (56.8%), poor results of laboratory tests (SGOT, SGPT), patients with all level of hepatic function based on Child-Pugh classification and staging B of the tumor (70.5%). Patients with normal AFP â‰¤20 ng/ml were dominated by female patients, with the most common etiology of fatty liver and others, and with BCLC A and C staging. Descriptively, there was no difference in AFP level based on the number of nodules and size of tumor. Conclusion: The most common patients with high AFP level are those who have hepatitis B as etiology, younger age, male gender, high SGOT level and BCLC B staging. Meanwhile, patients with normal AFP level dominated with female and non-hepatitis patients. In this research, we found no differences of AFP level based on number and size of tumor descriptively.